2007
DOI: 10.1002/dvdy.21312
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the murine retinol dehydrogenase 10 (Rdh10) gene correlates with many sites of retinoid signalling during embryogenesis and organ differentiation

Abstract: Retinoic acid acts as a signalling molecule regulating many developmental events in vertebrates. As this molecule directly influences gene expression by activating nuclear receptors, its patterns of synthesis have to be tightly regulated, and it is well established that at least three retinaldehyde dehydrogenases (RALDHs) are involved in such tissue-specific synthesis. Whereas embryos from oviparous species can obtain retinaldehyde by metabolizing carotenoids stored in the yolk, placental embryos rely on retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 71 publications
5
50
0
Order By: Relevance
“…Our findings are consistent with the expression of these enzymes during embryonic development, where ADH3 is detected in mouse pre-implantation embryo [20], and RDH10 and RDH1 in early postimplantation embryo [21][22][23]. RDH10 mutant mice display embryonic lethality at 13.5 d.p.c., and this is the earliest phenotype observed for a single retinol-metabolizing enzyme-deficient mouse [24].…”
Section: Expression Of Atra Biosynthetic Pathway Components During Spsupporting
confidence: 89%
“…Our findings are consistent with the expression of these enzymes during embryonic development, where ADH3 is detected in mouse pre-implantation embryo [20], and RDH10 and RDH1 in early postimplantation embryo [21][22][23]. RDH10 mutant mice display embryonic lethality at 13.5 d.p.c., and this is the earliest phenotype observed for a single retinol-metabolizing enzyme-deficient mouse [24].…”
Section: Expression Of Atra Biosynthetic Pathway Components During Spsupporting
confidence: 89%
“…A multitude of cytosolic alcohol dehydrogenases and microsomal short-chain dehydrogenases/reductases (SDRs) (Duester et al, 2003;Lidén and Eriksson, 2006), as well as the recently identified CYP1B1 mono-oxygenase (Chambers et al, 2007), can mediate the first step of RA synthesis from vitamin A. Retinol dehydrogenase 10 (RDH10) is a member of the SDR family that oxidizes retinol into retinal (Wu et al, 2002;Wu et al, 2004) in an NAD + -dependent manner (Belyaeva et al, 2008), and exhibits tissue-specific expression at embryonic and foetal mouse stages (Sandell et al, 2007;Cammas et al, 2007;Romand et al, 2008). Analysis of an N-ethyl-N-nitrosourea-generated mutant called trex suggested an essential function of murine RDH10 for RA biosynthesis during limb, craniofacial and organ development (Sandell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Rdh10 was identified initially as a visual cycle enzyme (11). Subsequently, Rdh10 was correlated with multiple sites of atRA biosynthesis in the mouse embryo (12). The Rdh10-null mouse is embryonic lethal, and hypomorphs fail to develop a normal cortex, because of decreased but not absent atRA (13)(14)(15)(16).…”
mentioning
confidence: 99%